2012
DOI: 10.1016/j.ijnurstu.2011.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative pain assessment based on numeric ratings is not the same for patients and professionals: A cross-sectional study

Abstract: What is already known about the topic?Pain assessment is the foundation of pain management when a patient is experiencing postoperative pain. A frequent and thorough assessment of patients' pain by registered nurses provides information to achieve optimal pain relief. Clinical guidelines are developed for postoperative pain management based on the patient's pain score. In these guidelines different cut-off points are used to treat the pain. What this paper addsPatients and professionals do interpret the numeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(68 citation statements)
references
References 28 publications
3
60
0
5
Order By: Relevance
“…Multiple studies from diverse settings have consistently found that patient-reported scores do not accurately predict the desire for analgesic therapy. [5][6][7][8][9][10][11] In their article, Chang et al 1 corroborate these previous findings, with 51% of their subjects declining further analgesics at least once despite reporting a pain score of 5 or greater and 21% similarly declining analgesics despite a score of 7 or greater. The authors observe that "the large variability.reinforces the necessity of asking patients if they want additional medication rather than basing treatment decisions on patients' reported level of pain."…”
Section: What Are Pain Scores Measuring?mentioning
confidence: 67%
See 1 more Smart Citation
“…Multiple studies from diverse settings have consistently found that patient-reported scores do not accurately predict the desire for analgesic therapy. [5][6][7][8][9][10][11] In their article, Chang et al 1 corroborate these previous findings, with 51% of their subjects declining further analgesics at least once despite reporting a pain score of 5 or greater and 21% similarly declining analgesics despite a score of 7 or greater. The authors observe that "the large variability.reinforces the necessity of asking patients if they want additional medication rather than basing treatment decisions on patients' reported level of pain."…”
Section: What Are Pain Scores Measuring?mentioning
confidence: 67%
“…5,19 Some patients decline pain medications because of concerns about drug-associated adverse effects (eg, nausea, pruritus, constipation, not feeling in control), allergy, potential opioid addiction (even if unfounded), or the need to drive themselves home. [5][6][7]19 Still others want analgesia, but would prefer to leave the ED quickly with their prescription in hand and begin treatment in the comfort of their own home. Others reporting pain are established drug seekers for whom opioids should be appropriately refused, or have absolute or relative contraindications to opioid administration such as hypotension, respiratory impairment, allergy, or altered mentation.…”
Section: Do All Patients In Pain Want Analgesics?mentioning
confidence: 99%
“…It has repeatedly been demonstrated that medical staff commonly misjudge the pain intensity that patients are experiencing. 12,13 Therefore, the administration of analgesics should be adjusted according to the individual patient's reported pain scores and desire for additional medication. In the present study, we were able to demonstrate that patients undergoing minor surgeries typically received no or low doses of opioids.…”
Section: Discussionmentioning
confidence: 99%
“…These numbers are imposingly demonstrating on one hand how painful HNC surgery is and on the other hand might reflect that the medical staff is misjudging the pain intensity of HNC patients like is known in general for postoperative pain [13]. So far only some quality of life studies have called indirectly attention to the prevalence of relevant postoperative pain after HNC surgery as quality of life assessments typically include pain as one dimension.…”
Section: Discussionmentioning
confidence: 99%